The prognostic value of pre-diagnosis health-related quality of life on survival: a prospective cohort study of older Americans with lung cancer. - Pinheiro, Laura; Zagar, Timothy; Reeve, Bryce; Pinheiro, Laura C; Zagar, Timothy M; Reeve, Bryce B (Quality of Life Research, 2017)
Purpose: Health-related quality of life (HRQOL) after cancer diagnosis is prognostic for overall survival (OS). However, no studies have assessed if HRQOL before diagnosis is predictive for OS. The objective of this study was to determine the association between pre-lung cancer diagnosis HRQOL and OS.Methods: Our prospective cohort study used surveillance, epidemiology, and end results linked to the Medicare Health Outcomes Survey. We included 6290 individuals 65 years or older diagnosed with incident lung cancer from 1998 to 2013. We assessed the prognostic value of (1) short-form 36 summary component and domain-specific scores, (2) activities of daily living (ADL), and (3) two global HRQOL questions. Cox-proportional hazards models were used to examine associations between HRQOL and OS, adjusting for demographics, comorbid conditions, and clinical characteristics.Results: Worse pre-diagnosis HRQOL was significantly associated with greater risk of death across HRQOL measures. An above average physical or mental component summary score was associated with 16 and 24% decreases in the hazard of death, respectively (p < 0.0001). Being unable to perform ADLs, such as bathing oneself, was associated with an 89% increased hazard of death (p < 0.0001). Reporting "poor" versus "excellent" health was associated with a 74% increase in the hazard of death (p < 0.0001).Conclusion: This population-based study reinforces the importance of self-reported health status as a predictor for OS. Routine HRQOL screening may identify patients who could benefit from early interventions to improve HRQOL. Future studies should explore associations between changes in HRQOL before and after cancer diagnosis and OS.